An improvement scheme for pressure-swing distillation with and without heat integration through an intermediate connection to achieve energy savings. (2nd November 2018) - Wang, Yinglong; Ma, Kang; Yu, Mengxiao; Dai, Yao; Yuan, Rujia; Zhu, Zhaoyou; Gao, Jun
Highlights: The PSDIC was proposed for separating binary azeotropic mixture. The effect of partial heat integration on the PSDIC was investigated. Energy and TAC saving were achieved by PSDIC and PHIPSDIC compared with PSD process. Abstract: Pressure-swing distillation is widely studied in academia and industry. Energy consumption is a key criterion for judging whether a pressure-swing distillation is better than other distillation methods. An improved process with an intermediate connection was developed based on the two-column pressure-swing distillation for separating a binary azeotropic mixture to save energy and reduce the total annual cost. The proposed pressure-swing distillation was applied to three case systems, two minimum-boiling azeotropic mixtures of ethyl acetate/ethanol and methanol/chloroform and one maximum-boiling azeotropic mixture of ethylenediamine/water. According to our analysis, the proposed pressure-swing distillation and heat-integrated scheme can reduce energy consumption and total annual cost. The pressure-swing distillation with the intermediate connection is promising for saving energy. This advantage assists in promoting the application of pressure-swing distillation and overall energy savings in the chemical process industry. Graphical abstract: